EXPRESSION OF CONCERN: Use of wearable technologies in health promotion in Human Medicine students - Curo Yllaconza, Javier Eduardo; Valle Elescano, Renee Amparo; Vilchez Cuevas, Tania Luz; Velásquez Orellana, Mirelly; Tezén Campos, José Hugo; Salazar Montenegro, Jaime; Riquez Livia, Digmer Pablo; Peralta Loayza, Eleazar Fidel (EAI Endorsed Transactions on Pervasive Health and Technology, 2024)
Concerns have been raised over the peer review and editorial processes involving this article. The full notice can be found here:  https://doi.org/10.4108/eetpht.11.12765
Keywords: Wearable technologies; wearables; Health promotion; Physical activity; Healthy habits